Sexual Minorities, Religion, and Self-Rated Health in the United States - Cranney, Stephen (Journal for the scientific study of religion, 2024)
While religiosity has generally been found to be associated with health, sexual minority individuals are a theoretically unique population in the literature. Because of sample size issues, the extent to which sexual minority individuals differ from nonsexual minority individuals in the health and religion relationship has been difficult to comprehensively test; additionally, the theoretically germane but often hypothesized distinction between affirming and nonaffirming religions has remained largely untested. This study draws on the Cooperative Election Study, a nationally representative survey with a relatively large sexual minority sample (∼6600), and finds that (1) sexual minority individuals are less likely to affiliate with a religion; (2) sexual minority individuals report poorer health; (3) sexual minority individuals do enjoy an overall health benefit from religiosity, but this benefit is attenuated (compared to nonsexual minority individuals) in the case of affiliation; and (4) there is some ambiguous evidence for an affirming religiosity effect.